Study on the Correlation between Body Measurement and Feed Intake on the Growth Performance of Heifer and Calf at Different Topographical Locations - S. Syawal; B. P. Purwanto; I. G. Permana (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
Environmental conditions pose direct and indirect effects on animal growth. Animal growth itself can be defined in many ways, and one of the parameters is body growth. This study was conducted to determine the dimensions of body measurements such as shoulder height (SH), body length (BL), chest width (CW), and heart girth (HG) of calves and heifer located in high land, middle land, and low land. The number of calves and heifer used in this study was 121 and 131, respectively. Calipster and rondo ribbon were used to measure the body measurements while the Gompertz model was used to predict the growth parameters of mature age. The results indicated that the maturity age of cattle raised in the high land, middle land, and low land were 347.63 - 371.52 days, 377.58 days, and 465.69 days, respectively. The growth rate for all body measurements (SH, BL, CW, HG) was higher in the high land compared to the middle land and low land. The sequences of growth development obtained from the Gompertz analysis was SH, CW, HG, and BL. Heifer reaching earlier puberty or mature age will have better body size.